Solutions of Making the Smart Energy Consumption in the Buildings - Mirpadyab, Seyed Kasra; Fatahi Darbid, Zahra; Khalili Ardali, Atefeh; Malek Poor, Amin (Journal of History Culture and Art Research, 2017)
Energy sources in the world have diminished rapidly during the last few decades. The projections suggest that the world would suffer energy shortage in near future. This problem leads states, governments, non-governmental organizations as well as engineers and architects to increase ways of using energy efficiently. Building energy-friend structures would be a substantial contribution to saving energy. In order to identify these factors that will help us in this regard, in this study, we tried to identify the solutions and methods that would increase energy saving. For this purpose, this study benefits from the current literature and identifies the smart materials which can be applied in the architectural design.